End-of-life care for homeless people: A qualitative analysis exploring the challenges to access and provision of palliative care. (January 2018) - Shulman, Caroline; Hudson, Briony F; Low, Joseph; Hewett, Nigel; Daley, Julian; Kennedy, Peter; Davis, Sarah; Brophy, Niamh; Howard, Diana; Vivat, Bella; Stone, Patrick
Background: Being homeless or vulnerably housed is associated with death at a young age, frequently related to medical problems complicated by drug or alcohol dependence. Homeless people experience high symptom burden at the end of life, yet palliative care service use is limited. Aim: To explore the views and experiences of current and formerly homeless people, frontline homelessness staff (from hostels, day centres and outreach teams) and health- and social-care providers, regarding challenges to supporting homeless people with advanced ill health, and to make suggestions for improving care. Design: Thematic analysis of data collected using focus groups and interviews. Participants: Single homeless people ( n  = 28), formerly homeless people ( n  = 10), health- and social-care providers ( n  = 48), hostel staff ( n  = 30) and outreach staff ( n  = 10). Results: This research documents growing concern that many homeless people are dying in unsupported, unacceptable situations. It highlights the complexities of identifying who is palliative and lack of appropriate places of care for people who are homeless with high support needs, particularly in combination with substance misuse issues. Conclusion: Due to the lack of alternatives, homeless people with advanced ill health often remain in hostels. Conflict between the recovery-focused nature of many services and the realities of health and illness for often young homeless people result in a lack of person-centred care. Greater multidisciplinary working, extended in-reach into hostels from health and social services and training for all professional groups along with more access to appropriate supported accommodation are required to improve care for homeless people with advanced ill health.